Experiences and needs of physiotherapists and exercise therapists regarding the management of working people with complaints of the arm, neck and shoulder (CANS): A focus group study. (December 2022) - Brunnekreef, Jaap J.; Feleus, Anita; Miedema, Harald S.; Staal, J. Bart; Hutting, Nathan
Abstract: Background: Non-traumatic complaints of the arm, neck and/or shoulder (CANS) are difficult-to-treat musculoskeletal conditions. CANS treatment has varying degrees of success, particularly in the working population. Objectives: To evaluate the experiences and needs of physiotherapists (PTs) and exercise therapists (ETs) regarding the treatment of working patients with CANS. Design: An exploratory qualitative focus group study was conducted. Method: Qualitative data were collected from 27 therapists who were purposefully recruited for their broad range of experience and qualifications. The data was analysed using thematic analysis. Results: Both PTs and ETs assess CANS extensively by exploring their patients' psychosocial factors, work-related factors, illness beliefs, and working conditions. Therapists apply hands-off treatment interventions, such as coaching the patient to make behavioural changes and providing self-management support. However, therapists experience many difficulties in these areas, resulting in a need to learn more about coaching techniques for behavioural change, engaging in meaningful conversations about the patient's perspective, supporting patients in building a strong social network in the workplace, and creating a professional network for collaboration. Conclusions: The treatment of working people with CANS is difficult for PTs and ETs. Therapists express a need to learn more about supporting self-management, applying coaching techniques and engaging in meaningful conversations. Moreover, therapists indicate a need to establish a professional multidisciplinary network to support collaborations with other disciplines to treat working patients with CANS . Highlights: The treatment of CANS is challenging for physiotherapists and exercise therapists. Therapists express a need to learn more about providing self-management support. Therapists want to learn more about how to coach patients to make behavioural changes. Therapists find it difficult to create a multidisciplinary network to collaborate with.